2016
DOI: 10.1136/bmjopen-2015-010380
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of energy drinks by children and young people: a rapid review examining evidence of physical effects and consumer attitudes

Abstract: ObjectiveTo examine patterns of energy drink consumption by children and young people, attitudes towards these drinks, and any associations with health or other outcomes.DesignRapid evidence assessment and narrative synthesis.Data sources9 electronic bibliographic databases, reference lists of relevant studies and searches of the internet.ResultsA total of 410 studies were located, with 46 meeting the inclusion criteria. The majority employed a cross-sectional design, involved participants aged 11–18 years, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
140
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(155 citation statements)
references
References 73 publications
11
140
0
4
Order By: Relevance
“…For instance, although an umbrella analysis conducted by Grosso et al (12) reported that coffee and caffeine intake are typically associated with health benefits in adults, findings from the current study showed that high caffeine consumption was (at least at the cross-sectional level) associated with low general health, and that caffeine intake from coffee was not associated with health at all. The observation that caffeine consumed from cola and energy drinks appeared to explain the negative associations is also in line with the findings of a recent review article by Visram et al (36). This paper showed that energy drink consumption in children and young people was associated with higher risk of health-damaging behaviors and physical health symptoms, such as headaches, stomachaches, insomnia, and hyperactivity, and suggested that such effects might be dose-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, although an umbrella analysis conducted by Grosso et al (12) reported that coffee and caffeine intake are typically associated with health benefits in adults, findings from the current study showed that high caffeine consumption was (at least at the cross-sectional level) associated with low general health, and that caffeine intake from coffee was not associated with health at all. The observation that caffeine consumed from cola and energy drinks appeared to explain the negative associations is also in line with the findings of a recent review article by Visram et al (36). This paper showed that energy drink consumption in children and young people was associated with higher risk of health-damaging behaviors and physical health symptoms, such as headaches, stomachaches, insomnia, and hyperactivity, and suggested that such effects might be dose-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…Visram et al . () found energy drink consumption to be positively associated with alcohol use, smoking and susceptibility to other substance use, consistent with findings from an earlier review that consumption of energy drinks amongst adolescents was associated with sensation seeking, binge‐drinking, smoking and use of other harmful substances (Breda et al . ).…”
Section: Research On Effects Of Energy Drinks In Childrensupporting
confidence: 87%
“…As with research on caffeine intake in children, studies of the impact of energy drinks on the health of children <16 years of age are limited. A recent review of the physical effects and consumer attitudes of energy drink consumption in children and young people highlighted the heterogeneity of studies in this area, noting that many were cross-sectional in design and relied on self-reported data (Visram et al 2016). Of the 410 studies identified within the review, 46 met the criteria for inclusion (i.e.…”
Section: Research On Effects Of Energy Drinks In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…So-called ‘rapid reviews’ have been published in a variety of clinical areas, including digital communication,1 children’s consumption of energy drinks,2 sexual health interventions,3 and cannabis cessation 3. Guideline developers have also used them.…”
mentioning
confidence: 99%